University Students’ Perception of the Huru Ai Interview Prep App in Increasing Students’ Preparedness For Job Interviews - Salsabila, Annisa Rizqika; Hadi, Muhammad Sofian (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study analyzes how artificial intelligence (AI) can be applied in educational settings, with a specific focus on career preparation via English-language job interview preparation. The study looks at how well AI-based programs, especially the Huru AI Interview Prep App, simulate job interviews in light of the importance of professional readiness in higher education. Data were gathered using a mixed-methods approach by distributing questionnaires with 15 statements to 31 respondents. In response to the results, 58% of students said that using AI tools, such as the Huru AI Interview Prep App, improved their ability to answer English-language job interview questions, which had a beneficial effect on their career preparation. Furthermore, four students participated in qualitative interviews using seven questions, which supported the quantitative findings and showed that AI-assisted job interview training greatly enhances students' English language skills and general preparedness for the workforce.